Search for Scalar Bottom Quark Pair Production with the ATLAS Detector in pp Collisions at √s = 7 TeV - Anduaga, Xabier Sebastián (2012)
The results of a search for pair production of the scalar partners of bottom quarks in 2.05 fb⁻¹ of pp collisions at √s = 7 TeV using the ATLAS experiment are reported. Scalar bottom quarks are searched for in events with large missing transverse momentum and two jets in the final state, where both jets are identified as originating from a bottom quark. In an R-parity conserving minimal supersymmetric scenario, assuming that the scalar bottom quark decays exclusively into a bottom quark and a neutralino, ~ 01 mass plane such that for neutralino masses 95% confidence-level upper limits are obtained in the b͞1 −͞X01 below 60 GeV scalar bottom masses up to 390 GeV are excluded.